IMPROVING JUNIOR HIGH SCHOOL STUDENTS’ VOCABULARY ACHIEVEMENT IN READING BY APPLYING WORD WALL - Devi Monita; Lince Sihombing (TRANSFORM : Journal of English Language Teaching and Learning, 2013)
AbstractThis study focused on Improving Junior High School Students’ Vocabulary Achievementin reading by Applying Word Wall. This study was conducted by using classroom actionresearch. The subject of this study was grade eight students of SMP Swasta KesumaIndah Padangsidimpuan. There were 38 students taken as the subject. This research wasdone in two cycles, each cycle consisted of three meetings. The instrument for collectingdata were the students’ performance score as the quantitative data and diary notes,observation sheet, and interview sheet as the qualitative data. Based on the data, it wasfound that the mean of students’ score increased from performance 1 until performance 3.The mean of students’ score in performance 1 was 65.16. The mean of students’ score inperformance 2 was 73.39. The mean of students’ score in performance 3 was 78.11. It canbe concluded that the application of word wall had successfully improved the students’vocabulary achievement in reading.Key Words: Vocabulary, Reading, Performance, Data, Classroom ActionResearch